New wonder of an old hormone: Hungarian sour cherry varieties as natural melatonin sources - Homoki, Judit; Gyémánt, Gyöngyi; Remenyik, Judit (Acta Agraria Debreceniensis, 2015)
Agriculture has always been an important role in economy, food supplies, sustainability of society During our experimental work an effective extraction procedure has been developed for melatonin. Further chromatography was developed the quantitative and qualitative determination of melatonin. A compound that was equal to the standard was purified from the extract by preparative HPLC technique and the structure of the purified sample was confirmed by MALDI-TOF-MS and NMR analysis. Based on our measurements, harvested in the state of biological maturity Hungarian sour cherry cultivars contain high levels of melatonin. Our results show that "VN4" variety has extremely high melatonin content, 9.893 ug g-1 and suggest that "VN4" which were selected from the "Bosnyák" varieties is melatonin accumulating. The average value of the melatonin content of Hungarian sour cherry cultivars is 2.319 ug g-1.